2018
DOI: 10.1519/jsc.0000000000002247
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Fish Oil Supplementation in Attenuating Exercise-Induced Muscle Damage in Women During Midfollicular and Midluteal Menstrual Phases

Abstract: McKinley-Barnard, SK, Andre, TL, Gann, JJ, Hwang, PS, and Willoughby, DS. Effectiveness of fish oil supplementation in attenuating exercise-induced muscle damage in females during midfollicular and midluteal menstrual phases. J Strength Cond Res 32(6): 1601-1612, 2018-The purpose of this study was to determine whether the differences in estrogen levels during the female menstrual cycle and fish oil supplementation would attenuate eccentric exercise-induced muscle damage and delayed-onset muscle soreness (DOMS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 36 publications
0
19
2
Order By: Relevance
“…One prominent difference between the Tinsley et al investigation and our study is that we employed a seven-week run-in the supplementation period prior to inducing muscle damage, while their experimental design included supplementation for seven days prior to the damaging exercise bout. To add, and in contrast to our findings, an investigation by McKinely-Barnard et al [ 40 ] found that 6G per day FO for 21 days resulted in higher perceived soreness ratings by young women 6- and 24-H post-eccentric exercise when compared to PL. Interestingly, the investigation utilized the same supplementation (FO and PL brands) as our study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…One prominent difference between the Tinsley et al investigation and our study is that we employed a seven-week run-in the supplementation period prior to inducing muscle damage, while their experimental design included supplementation for seven days prior to the damaging exercise bout. To add, and in contrast to our findings, an investigation by McKinely-Barnard et al [ 40 ] found that 6G per day FO for 21 days resulted in higher perceived soreness ratings by young women 6- and 24-H post-eccentric exercise when compared to PL. Interestingly, the investigation utilized the same supplementation (FO and PL brands) as our study.…”
Section: Discussioncontrasting
confidence: 99%
“…While previous research has indicated FO supplementation may attenuate losses in muscular strength following vigorous exercise [35,54,55], our results do not support these findings, which is similar to the majority of research to date [34,40,41,53,55]. It is thought that FO may reduce the amount of damage assumed by the worked skeletal muscle and conserve strength and power production, and thus muscular performance.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Another recent study measured the impact of medium term (21 days prior to muscle damage) n-3PUFA supplementation on indices of recovery following muscle damaging exercise in females (McKinley-Barnard et al, 2018). Participants consumed either 4.2 g/day of n-3PUFA or a placebo supplement consisting of safflower oil for 21 days before undergoing a bout of intense eccentric exercise.…”
Section: Team-based Athletesmentioning
confidence: 99%
“…As outlined in Table 3 , one study assessed omega-3-fatty acids [ 41 ], and nine studies assessed phytochemical-based dietary supplement interventions [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. Three of these studies originated from the United Kingdom [ 42 , 45 , 47 ], three from Spain [ 43 , 44 , 46 ], three from Australia [ 48 , 49 , 50 ], and one from the United States [ 41 ].…”
Section: Resultsmentioning
confidence: 99%